Lived experiences of sixth grade teachers and students from the qualitative assessment of math lessons, designing a scale of teacher skills in the qualitative evaluation of math lessons - Masoud hosseini; Abolfazl Tehranian; Mohammad Hassan Behzadi; Seyyed Hassan Alam Al-Hadaei (مجله علوم روانشناختی)
Background: The existing research in this field indicates that there has been insufficient investigation into the life experiences of sixth-grade teachers and students concerning the qualitative values of mathematics lessons. Furthermore, there is a noticeable gap in the development of a scale for assessing teaching skills in the qualitative evaluation of mathematics lessons. This highlights the need for comprehensive studies that explore the lived experiences of both teachers and students in the context of qualitative values within mathematics education, along with the design of an effective scale to assess teaching skills in the qualitative evaluation of mathematics lessons. Aims: The purpose of this research was to investigate the lived experiences of sixth grade teachers and students of the qualitative value of math lessons. Methods: The current research was applied in terms of purpose and qualitative in terms of method and based on phenomenological strategy. The participants of this research were sixth grade teachers and students who were selected by purposive sampling. The tool used in this research was a semi-structured interview. In order to analyze the data, the coding method was used. Results: the results showed that the interviewees suffered from disadvantages such as lack of belief in qualitative evaluation, teachers' lack of knowledge about the philosophy of qualitative evaluation, the spirit of evaluation not being governed, and the inability of students to measure by themselves., the growth of teachers in the evaluation system has been mentioned a little. Also, teachers suffer from harms such as the reduction of healthy competition, children's insensitivity to lessons, low motivation, and lack of proper infrastructure, carelessness, students not studying, lack of enthusiasm and attractiveness in teachers, and the inability to cover weaknesses in evaluation. Qualitatively pointed out. Conclusion: The aim of the current research was to investigate the lived experiences of sixth grade teachers and students of the qualitative evaluation of mathematics lessons, to design a scale of teacher skills in the qualitative evaluation of mathematics lessons. The results of data analysis showed that from the teachers' point of view, 23 main categories and 60 sub-categories, and from the students' point of view, 21 main categories and 42 sub-categories were identified as necessary factors and components and obstacles and challenges for the implementation of qualitative evaluation.